PO27 Promising plant species from the Colombian Pacific: Characterization and scientific value - Sanchez Marin, Francisco Jose; Chalá Grueso, Brenda Briyi; Angulo Pinillo, Jhon Eduard; Angulo Rodríguez, María Elena; Cardona Montoya, josé Omar (Revista Productos Naturales, 2025)
The plants used locally are found in the gardens and rooftops of the inhabitants; being important for their medicinal and magical-religious power. This study was conducted because promising species are losing their scientific value and ancestral knowledge. The objective was to determine the scientific value of species of the genus Piper in the central subregion of the Colombian Pacific through phytochemical markers.